1991
DOI: 10.2307/1943001
|View full text |Cite
|
Sign up to set email alerts
|

Models and Mechanisms of Succession: An Example From a Rocky Intertidal Community

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 139.184.Abstract. An investigation of the processes that cause succession was performed in an intertidal community on the central Oregon coast. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
209
6
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(229 citation statements)
references
References 85 publications
(209 reference statements)
9
209
6
5
Order By: Relevance
“…Tests remain affixed to the surface after the organism dies (and may persist for several months and years) making them particularly practical targets for a laboratory study. Furthermore, the establishment of barnacles is an important early step in the development of diverse benthic communities (Farrell, 1991;Harley, 2006;Tews et al, 2004;Thompson et al, 1996), and there is considerable opportunity to facilitate their settlement and recruitment to engineered surfaces (for ecological gain) using simple textural manipulation (Coombes et al, 2015a). The influence of barnacles on deterioration processes, such as thermal degradation and salt weathering, is therefore an important question we aimed to address.…”
Section: Aims and Approachmentioning
confidence: 99%
“…Tests remain affixed to the surface after the organism dies (and may persist for several months and years) making them particularly practical targets for a laboratory study. Furthermore, the establishment of barnacles is an important early step in the development of diverse benthic communities (Farrell, 1991;Harley, 2006;Tews et al, 2004;Thompson et al, 1996), and there is considerable opportunity to facilitate their settlement and recruitment to engineered surfaces (for ecological gain) using simple textural manipulation (Coombes et al, 2015a). The influence of barnacles on deterioration processes, such as thermal degradation and salt weathering, is therefore an important question we aimed to address.…”
Section: Aims and Approachmentioning
confidence: 99%
“…Recovery patterns, which are influenced by the external environment, recruitment rates, and species interactions (30,31), can lend insight into these important community dynamics. Highly variable and idiosyncratic recovery patterns (i.e., contingent succession, sensu ref.…”
mentioning
confidence: 99%
“…32) suggest that recovery is dependent on recruitment patterns and species interactions that vary either spatially and/or temporally (33). However, strong predictable species interactions can also cause succession to be canalized (32), in which disturbed assemblages converge on a predictable community over time (30,31,34). This pattern of predictable species interactions and canalized succession could be driven by harsh environmental conditions, such as ocean acidification, in which species that can tolerate or benefit from the extreme conditions are the only species that are able to persist through time (35,36).…”
mentioning
confidence: 99%
“…Increased recruitment and abundance of Mytilus edulis (one of two species of mussels recorded during this study) and Brachidontes rostratus have been observed at locations where sewage is present (Dakin, 1987;Hindell and Quinn, 2000). Furthermore, barnacles are rapid colonisers 25 and may delay succession of grazers (Sutherland and Karlson, 1977;Farrell, 1991;Mann, 2000).…”
Section: Bush Locations Were Dominated By Bembicium Auratum Saccostrmentioning
confidence: 99%